2022
DOI: 10.33096/whj.v3i2.86
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Karakteristik Penderita Otitis Eksterna

Abstract: Latar belakang: Otitis eksterna adalah suatu inflamasi dari saluran telinga bagian luar, terbagi atas otitis eksterna akut (otitis eksterna sirkumkripta, otitis eksterna difusa) dan otitis eksterna kronik. Kejadian otitis eksterna disebabkan berbagai faktor predisposisi tertentu, seperti perubahan pH kanalis dari asam menjadi basa dan trauma ringan akibat membersihkan telinga secara berlebihan. Tujuan: Untuk mengetahui karakteristik penderita otitis eksterna. Metode: Penelitian yang dilakukan adalah Literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
3
0
4
Order By: Relevance
“…Allegedly, sufferers use their right hand more often than their left hand to clean their ears by carrying out one of the predisposing factors for otitis externa, namely by picking the ear. 2,17 Although the majority of otitis externa patients in this study did not have comorbidities, the most common comorbid disease found in otitis externa patients who had comorbidities was diabetes mellitus, which is a risk factor for otitis externa.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Allegedly, sufferers use their right hand more often than their left hand to clean their ears by carrying out one of the predisposing factors for otitis externa, namely by picking the ear. 2,17 Although the majority of otitis externa patients in this study did not have comorbidities, the most common comorbid disease found in otitis externa patients who had comorbidities was diabetes mellitus, which is a risk factor for otitis externa.…”
Section: Discussionmentioning
confidence: 77%
“…Adam Malik Medan also showed that the location of the most involved ear was the right ear, namely 19 cases (50%), followed by the left ear as many as 16 cases (42.1%), and at least both ears (bilateral) only 3 cases (7.9%). 17 There is no definite reason to support this result. Allegedly, sufferers use their right hand more often than their left hand to clean their ears by carrying out one of the predisposing factors for otitis externa, namely by picking the ear.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Penggunaan alat tersebut akan mendorong serumen lebih jauh ke dalam sehingga penggunaan secara terus-menerus dapat memicu peradangan atau infeksi yang pada akhirnya berkontribusi terhadap perkembangan otitis eksterna (5).…”
Section: Staphylococcus Aureus (3)unclassified
“…Kasus otitis eksterna paling banyak terjadi pada kelompok usia orang dewasa, dan jarang pada kelompok usia anakanak. Penelitian ini menjelaskan bahwa kejadian otitis eksterna dapat terjadi pada semua kelompok umur (5).…”
Section: Pembahasanunclassified